Selective removal of heavy metals using novel active carbons - Vladimir Strelko (1999)
Porous carbonaceous adsorbent materials possessing weakly acidic surface functional groups have been evaluated for the selective removal of heavy metals from aqueous solutions. Active carbons derived from both agricultural products (KAU carbons) and polymeric resin (CKC carbon) have been oxidised by hot air or nitric acid to produce samples with different degrees of surface oxidation. A novel phosphorus-containing carbonaceous sorbent (PGP-P) has been prepared by pyrolysis of phosphorylated phenol-formaldehyde resin. Surface modifications have been carried out to introduce various acidic functional groups capable of selective heavy metal binding. The properties of these sorbents have been compared to those of commercially available polymeric carboxylic resin C 104 (Purolite) and oxidised Filtrasorb 400 (Chemviron). Investigation into the physical structure of the adsorbents using microscopy and nitrogen sorption at liquid nitrogen temperatures showed that the porous structure is adversely affected by carbon oxidation. The surface area and pore volume decrease as the degree of surface oxidation increases. The low surface area and pore volume of PGP-P was attributed to the presence of phosphorus-containing functional groups which protect the surface from excessive burn-off. The surface functionality of the sorbcnts was determined by FT-IR, NMR and X-ray photoelectron spectroscopy. Relatively high concentrations of different weakly acidic functional groups were detected on the surface of the materials studied. The ion-exchange properties of the sorbents were assessed by acid-base titration techniques and electrophoretic mobility measurements. Oxidation of carbons with hot air resulted in a greater proportion of relatively weaker type surface functionality (i.e. phenolic) whereas nitric acid modification produced a higher concentration of relatively stronger carboxylic groups. Electrophoretic mobility measurements suggested that the carbon surface is negatively charged within the range of pH values studied. pH titration results demonstrated relatively greater surface acidity of active carbons compared to carboxylic resin. Active carbons were successfully applied for the selective removal of radionuclides. The materials showed excellent decontamination factors for a-, b- and y emitters. This was attributed to the presence of mineral admixtures and humic acids in carbons as well as the surface functional groups. Repeated cycles of lead sorption/elution indicated that the metal capacities of the carbon-packed mini-columns were reduced but reached a steady level after 3-4 cycles.